Ultimate unofficial Minecraft challenge a collection of creative, collaborative projects that connect in-game challenges with hands-on activities - Miller, John 1962-; Scott, Chris Fornell (Quarry, 2024)
Unlock Minecraft's powerful potential as a teaching tool with these engaging in-world and real-world activities for kids! Written by two experienced educators who have successfully used Minecraft in their classrooms, Ultimate Unofficial Minecraft Challenge teams in-game builds and other projects with out-of-game, hands-on activities to create fun adventures in learning. Adapted from the authors' popular and well-reviewed Unofficial Minecraft Lab for Kids and Unofficial Minecraft STEM Lab for Kids, Ultimate Unofficial Minecraft Challenge offers a series of exciting "labs" or lessons across a range of subjects, including STEM (science, technology, engineering, and math), art, culture, and history. Create shadow puppets to perform a scene from a favorite story, then recreate and animate a movie scene using Minecraft. Grow crystals using a super-saturated salt solution, then build a crystal castle in-game. Fold and fly paper airplanes, then let your imagination run wild while crafting airships in Minecraft. Concoct glow-in-the-dark goo, then set up a colorful light spectrum in-game using beacons. And more! Kids ages 7 to 11 and their families will especially enjoy this fun and unique approach to learning about Minecraft as an educational tool and working on art and craft activities or STEM experiments together.
Includes index. - Print version record
Keywords: Minecraft (Video game) -- Juvenile literature; Handicraft -- Juvenile literature; Science projects -- Juvenile literature; Artisanat; Ouvrages pour la jeunesse; Sciences; Travaux pratiques; Ouvrages pour la jeunesse; Crafts & Hobbies; JUVENILE NONFICTION; General (see also headings under Animals or Technology); Experiments & Projects; Self-Esteem & Self-Reliance; General (see also headings under Family); Games & Activities